Diversity of Anaplasma species in cattle in Mozambique - Fernandes, Simone de Jesus [UNESP] (2019)
Although species of Anaplasma are highly prevalent Rickettsiales agents in domestic and wild ruminants with a wide distribution worldwide, few studies have been conducted so far to detect and/or investigate the diversity of these agentsin cattle in Mozambique. In the present study, serological and molecular assays were used to investigate the occurrence of Anaplasma spp. in 219 bovines sampled in the districts of Boane, Magude, Matutuíne, Moamba and Namaacha in Maputo, Mozambique. In the iELISA test for detection ofIgG antibodies to A. marginale, 86.3% (189/219) of the samples were positive. In qPCR assays for the gene msp1β for A. marginale and msp2 for A. phagocytophilum, 97.3% (213/219) and 2.7% (6/219) of the animals were positive, respectively. Two different cPCR protocols based on the 16S rRNA gene showed that 100% of the samples were positive for Anaplasma spp. The DNA sequences obtained were phylogenetically related to A. platys, A. phagocytophilum, Candidatus Anaplasma boleense, A. centrale, A. marginale and A. ovis. Phylogenetic inference based on the msp4 and msp5 genes positioned the obtained sequences in the clade of A. marginale, with evidence of occurrence of 8 and 5 different haplotypes for each gene, respectively. Anaplasma sp. phylogenetically associated with A. platys was evidenced in phylogenetic analyzes based on 16S rRNA and groEL genes. It is concluded that a high diversity of species of Anaplasma spp. occurs in cattle in Mozambique.